2016
DOI: 10.1021/acs.molpharmaceut.6b00396
|View full text |Cite
|
Sign up to set email alerts
|

Use of HμREL Human Coculture System for Prediction of Intrinsic Clearance and Metabolite Formation for Slowly Metabolized Compounds

Abstract: Design of slowly metabolized compounds is an important goal in many drug discovery projects. Standard hepatocyte suspension intrinsic clearance (CLint) methods can only provide reliable CLint values above 2.5 μL/min/million cells. A method that permits extended incubation time with maintained performance and metabolic activity of the in vitro system is warranted to allow in vivo clearance predictions and metabolite identification of slowly metabolized drugs. The aim of this study was to evaluate the static HμR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…All infections were carried out between 7–10 days following plating at a point previously determined as optimal for restoring hepatic functions in the cultures 29, 32, 33 . To determine whether the time point of initial HBV infection could possibly be extended further, we challenged mixed donor SACC-PHHs with HBVcc 10, 15, or 20 days post-plating (schematic Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All infections were carried out between 7–10 days following plating at a point previously determined as optimal for restoring hepatic functions in the cultures 29, 32, 33 . To determine whether the time point of initial HBV infection could possibly be extended further, we challenged mixed donor SACC-PHHs with HBVcc 10, 15, or 20 days post-plating (schematic Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that CL int, in vitro estimated using the relay method showed excellent predictions of human CL int, in vivo . Further, novel in vitro systems such as HepatoPac 44,45) and HμREL, 46,47) which are micropatterned hepatocyte coculture systems, and cell systems such as upcyte, 48) which is derived from human hepatocytes, have been used to estimate low CL int, in vitro and predict in vivo CL in humans.…”
Section: Prediction Of Human Pk Using Ivivementioning
confidence: 99%
“…The physiological human scaling factors were 120 million cells/g liver, 25.7 g liver/kg body weight and 21 mL/min/kg of liver blood flow (Q h ). Fraction unbound in plasma ( f u,p ) and the blood to plasma ratio (R b ) were obtained from the literature, 4,[15][16][17][18] and each fraction unbound in blood ( f b ) was calculated by dividing the value of f u,p by that of R b . The protein binding rate in metabolic culture medium or adherent cells ( f u,inc ) was assumed to be 1.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…However, when hepatocytes are used in suspension assay, metabolic activity or hepatic function are drastically reduced within several hours. Further, the number of slowly metabolized drug candidates, which are difficult to evaluate in conventional assay systems, are increasing in the field of drug discovery, thus, evaluation methods for low CL drug candidates such as the Relay method 3) and co-culture system 4,5) have been developed. In addition, human PK prediction using chimeric mice has attracted attention, and their use in drug discovery has increased.…”
Section: Introductionmentioning
confidence: 99%